In figure, $ \mathrm{ABC} $ and $ \mathrm{BDE} $ are two equilateral triangles such that $ \mathrm{D} $ is the mid-point of $ \mathrm{BC} $. If $ \mathrm{AE} $ intersects $ \mathrm{BC} $ at $ \mathrm{F} $, show that
(i) $ \operatorname{ar}(\mathrm{BDE})=\frac{1}{4} \operatorname{ar}(\mathrm{ABC}) $
(ii) $ \operatorname{ar}(\mathrm{BDE})=\frac{1}{2} \operatorname{ar}(\mathrm{BAE}) $
(iii) $ \operatorname{ar}(\mathrm{ABC})=2 $ ar $ (\mathrm{BEC}) $
(iv) $ \operatorname{ar}(\mathrm{BFE})=\operatorname{ar}(\mathrm{AFD}) $
(v) $ \operatorname{ar}(\mathrm{BFE})=2 \operatorname{ar}(\mathrm{FED}) $
(vi) $ \operatorname{ar}(\mathrm{FED})=\frac{1}{8} \operatorname{ar}(\mathrm{AFC}) $

[Hint: Join $ \mathrm{EC} $ and $ \mathrm{AD} $. Show that $ \mathrm{BE} \| \mathrm{AC} $ and $ \mathrm{DE} \| \mathrm{AB} $

AcademicMathematicsNCERTClass 9

Given:

 \( \mathrm{ABC} \) and \( \mathrm{BDE} \) are two equilateral triangles such that \( \mathrm{D} \) is the mid-point of \( \mathrm{BC} \).

\( \mathrm{AE} \) intersects \( \mathrm{BC} \)

To do:

We have to show that

(i) \( \operatorname{ar}(\mathrm{BDE})=\frac{1}{4} \operatorname{ar}(\mathrm{ABC}) \)
(ii) \( \operatorname{ar}(\mathrm{BDE})=\frac{1}{2} \operatorname{ar}(\mathrm{BAE}) \)
(iii) \( \operatorname{ar}(\mathrm{ABC})=2 \) ar \( (\mathrm{BEC}) \)
(iv) \( \operatorname{ar}(\mathrm{BFE})=\operatorname{ar}(\mathrm{AFD}) \)
(v) \( \operatorname{ar}(\mathrm{BFE})=2 \operatorname{ar}(\mathrm{FED}) \)
(vi) \( \operatorname{ar}(\mathrm{FED})=\frac{1}{8} \operatorname{ar}(\mathrm{AFC}) \)

Solution:

Join \( \mathrm{EC} \) and \( \mathrm{AD} \)

"Screenshot

Let $G$ and $H$ be the mid-points of the sides $AB$ and $AC$ respectively.

Join $G$ and $H$.

$GH$ is parallel $BC$.

This implies, by mid point theorem,

$GH=\frac{1}{2}BC$

$GH=BD=DC$

Similarly,

$GD = AH = CH$

$DH = AG = BG$

This implies,

$\triangle ABC$ is divided into four equal equilateral triangles $\triangle BGD, \triangle AGH, \triangle DHC$ and $\triangle GHD$

Therefore,

$\triangle BGD=\frac{1}{4}\triangle ABC$

In $\triangle BDG$ and $\triangle BDE$

$BG=BE$

$BD=BD$

$DG=DE$

Therefore, by SSS congruency,

$\triangle BDG \cong \triangle BDE$

This implies,

$ar(\triangle BDG)=ar(\triangle BDE)$

$ar(\triangle BDE)=\frac{1}{4}ar(\triangle ABC)$

(ii)

 "Screenshot

$\triangle BDE$ and $\triangle AED$ have common base $DE$ and $DE \| AB$

This implies,

$ar(\triangle BDE) = ar(\triangle AED)$

$ar(\triangle BDE)−ar(\triangle FED) = ar(\triangle AED)−ar (\triangle FED)$

$ar(\triangle BEF) = ar(\triangle AFD)$.......…(i)

$ar(\triangle ABD) = ar(\triangle ABF)+ar(\triangle AFD)$

$ar(\triangle ABD) = ar(\triangle ABF)+ar(\triangle BEF)$         [From (i)]

$ar(\triangle ABD) = ar(\triangle ABE)$........…(ii)

$AD$ is the median of $\triangle ABC$.

This implies,

$ar(\triangle ABD) =\frac{1}{2}ar (\triangle ABC)$

$= 4\times[\frac{1}{2}ar (\triangle BDE)]$

$= 2 ar(ΔBDE)$.......…(iii)

From (ii) and (iii), we get,

$2 ar (\triangle BDE) = ar (\triangle ABE)$

$ar (\triangle BDE) =\frac{1}{2} ar (\triangle BAE)$

(iii) $\triangle ABE$ and $\triangle BEC$ have common base $BE$ and $BE \| AC$

This implies,

$ar(\triangle ABE) = ar(\triangle BEC)$

$ar(\triangle ABF) + ar(\triangle BEF) = ar(\triangle BEC)$

$ar(\triangle ABF) + ar(\triangle AFD) = ar(\triangle BEC)$             [From (i)]

$ar(\triangle ABD) = ar(\triangle BEC)$

$\frac{1}{2}ar(\triangle ABC) = ar(\triangle BEC)$

$ar(\triangle ABC) = 2 ar(\triangle BEC)$

(iv) $\triangle BDE$ and $\triangle AED$ lie on the same base $DE$ and between the parallels $DE$ and $AB$.

This implies,

$ar (\triangle BDE) = ar (\triangle AED)$

Subtracting $ar(\triangle FED)$ from both sides, we get,

$ar (\triangle BDE)−ar (\triangle FED) = ar (\triangle AED)−ar (\triangle FED)$

$ar (\triangle BFE) = ar(\triangle AFD)$

(v) Let $h$ be the height from $E$ to the side $BD$ in $\triangle BDE$ and $H$ the height from $A$ to the side $BC$ in $\triangle ABC$.

$ar (\triangle BDE) = \frac{1}{4}ar (\triangle ABC)$          (Proved)

$ar (\triangle BFE) = ar (\triangle AFD)$           (Proved)

$ar (\triangle BFE) = ar (\triangle AFD)$

$ar(\triangle BFE)= 2 ar (\triangle FED)$

(vi) $ar (\triangle AFC) = ar (\triangle AFD) + ar(\triangle ADC)$

$= 2 ar (\triangle FED) + \frac{1}{2}ar(\triangle ABC)$

$= 2 ar (\triangle FED) +\frac{1}{2}[4ar(\triangle BDE)]$

$= 2 ar (\triangle FED) +2 ar(\triangle BDE)$

$\triangle BDE$ and $\triangle AED$ are on the same base and between the same parallels$

$= 2 ar (\triangle FED) +2 ar (\triangle AED)$

$= 2 ar (\triangle FED) +2 [ar (\triangle AFD) +ar (\triangle FED)]$

$= 2 ar (\triangle FED) +2 ar (\triangle AFD) +2 ar (\triangle FED)$

$= 4 ar (\triangle FED) +4 ar (\triangle FED)$

$ar (\triangle AFC) = 8 ar (\triangle FED)$

$ar (\triangle FED) = \frac{1}{8}ar (\triangle AFC)$

Hence proved.

raja
Updated on 10-Oct-2022 13:46:30

Advertisements